Wnt5A Signaling Blocks Progression of Experimental Visceral Leishmaniasis - Maity, Shreyasi; Chakraborty, Arijit; Mahata, Sushil Kumar; Roy, Syamal; Das, Anjan Kumar; Sen, Malini (Frontiers in Immunology, 2022)
Visceral Leishmaniasis, caused by L. donovani infection is fatal if left untreated. The intrinsic complexity of visceral leishmaniasis complicated further by the increasing emergence of drug resistant L. donovani strains warrants fresh investigations into host defense schemes that counter infections. Accordingly, in a mouse model of experimental visceral leishmaniasis we explored the utility of host Wnt5A in restraining L. donovani infection, using both antimony sensitive and antimony resistant L. donovani strains. We found that Wnt5A heterozygous (Wnt5A +/-) mice are more susceptible to L. donovani infection than their wild type (Wnt5A +/+) counterparts as depicted by the respective Leishman Donovan Units (LDU) enumerated from the liver and spleen harvested from infected mice. Higher LDU in Wnt5A +/- mice correlated with increased plasma gammaglobulin level, incidence of liver granuloma, and disorganization of splenic white pulp. Progression of infection in mice by both antimony sensitive and antimony resistant strains of L. donovani could be prevented by activation of Wnt5A signaling through intravenous administration of rWnt5A prior to L. donovani infection. Wnt5A mediated blockade of L. donovani infection correlated with the preservation of splenic macrophages and activated T cells, and a proinflammatory cytokine bias. Taken together our results indicate that while depletion of Wnt5A promotes susceptibility to visceral leishmaniasis, revamping Wnt5A signaling in the host is able to curb L. donovani infection irrespective of antimony sensitivity or resistance and mitigate the progression of disease.